A case study of mental health communication programme delivery during mass violence in southern Thailand, 2004-2014 : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Communication at Massey University, Manawatū, New Zealand - Buaniaw, Aruneewan (Massey University, 2017)
In response to long-term mass violence in southern Thailand, the Thai government set up the 12th Mental Health Centre (the key site of this study) in 2004 for mental health healing and rehabilitation, and to provide various mental health programmes for affected groups. This case study examines how those programmes were planned, implemented, and evaluated between 2004 and 2014. The successes and challenges of mental health communication programme delivery in such a situation were also identified. The development of Centre 12’s programme reflects different but interrelated policy shifts: the reactive programme (2004–2005); the targeted groups policy (2005–2010); the general age-group targets (2011–2014); and the emerging phase of severe and complicated cases (2014 on). Key findings showed four stages in Centre 12’s programme framework: planning, media/message development, implementation, and evaluation. Within these phases, Centre 12 largely focused on media/message development, reflecting the nature of the public relations work force in Thailand and concern with religion differences. Print materials were verified by experts and media were produced with cultural sensitivity. Religious-based booklets were deemed noteworthy because of the participatory process in media production, testing, and refinement. Interpersonal and group communications were the main delivery channels. Additionally, training programmes for deliverer groups such as public health practitioners, community leaders, religious leaders, teachers, and radio DJs were crucial because these groups were trusted by local people and could reduce suspicion. Programme evaluation was a significant challenge, shown in Centre 12’s difficulties measuring programme outcomes, impacts, and knowledge utilisation. The Centre 12 case also contains some lessons in delivery in a mass violence situation: mental health communication programmes should focus on community-based approaches and coordinate with community partners, informal, flexible styles of partnership are most suitable for uncertain situations, and programme deliverers need to be concerned with cultural sensitivities. Last, leadership is an important factor for disaster management; however, organisations should set a system of recovery rather than rely on an individual leader. This case study considers wider implications for the government, campaign planners, communication and health communication scholars and practitioners, and those facing similar circumstances in the current unstable geopolitical environment.
Keywords: Communication in public health; Mental health promotion|; Victims of violent crimes; Mental health services; Government policy; Thailand; Research Subject Categories::INTERDISCIPLINARY RESEARCH AREAS::Health and medical services in society